QUANTIFICATION OF MEAN PLATELET VOLUME IN DIABETIC PATIENTS PRESENTING WITH CEREBROVASCULAR DISEASES - Shahab, Khalid; Mehr, Muhammad Tariq; Marwat, Mumtaz Ali; Amanullah, . (Journal of Postgraduate Medical Institute, 2016)
Objective: To estimate the mean platelet volume (MPV) in the patients with diabetes who present to hospital with various cerebrovascular diseases. Methodology: It was a cross sectional descriptive study conducted in the Department of Medicine, Hayatabad Medical Complex (HMC), Peshawar from 1st June, 2014 till 30th Mar, 2015. A total of 137 adult patients between 25 to 75 years of age of either gender with Type 2 DM and stroke attending hospital were included. All patients with prior chronic kidney disease, chronic liver disease or with previous cerebrovascular events were excluded from the study. Under strict aseptic conditions, 10cc blood was obtained and sent immediately to hospital laboratory for measurement of MPV. Results: Among the 137 patients, 85 (62.04%) were females and 52(37.96%) were males. The average age of the patients was 53.01±11.97 years with range of 30-73 years. Average duration of DM in the patients was 5.15±2.87 years with range of 1-12 years. There were 65(47.45%) patients of the less than or equal to 4 years DM duration. Forty two (30.66%) patients were in the range of 5-7 years, 24 (17.52%) were in the 8-10 years range while 6(4.38%) presented with cerebrovascular accidents at more than 10 years of type 2 DM. There were 84 (61.3%) and 53(38.7%) patients having MPV greater than and less than 9.01 fl respectively (average MPV was 9.42±0.92). Conclusion: Increased MPV was found in a significant number of patients and was more in the males and patients with age greater than 50 years.